'The world is full of big bad wolves': investigating the experimental therapeutic spaces of R.D. Laing and Aaron Esterson. Issue 3 (September 2014) - McGeachan, Cheryl
In conjunction with the recent critical assessments of the life and work of R.D. Laing, this paper seeks to demonstrate what is revealed when Laing's work on families and created spaces of mental health care are examined through a geographical lens. The paper begins with an exploration of Laing's time at the Tavistock Clinic in London during the 1960s, and of the co-authored text with Aaron Esterson entitled, Sanity, Madness and the Family (1964). The study then seeks to demonstrate the importance Laing and his colleague placed on the time-space situatedness of patients and their worlds. Finally, an account is provided of Laing's and Esterson's spatial thinking in relation to their creation of both real and imagined spaces of therapeutic care.